Modulating OFC Activity With tDCS Alters Regret About Human Decision-Making - Yu, Ping; Lu, Xinbo; Chen, Yuyou; Ye, Hang; Zeng, Lulu; Guo, Wenmin (Frontiers in Psychology, 2021)
Regret is a common emotion in humans' daily life. Humans always regret their decision-making choices if the chosen outcome is bad. Neuroscientific studies suggest that the orbitofrontal cortex (OFC) influences feelings of regret. We used a transcranial direct current stimulation (tDCS) device to study the role of regret in participants’ decision-making by modulating the activity of the OFC. The two-wheel-of-fortune gamble task was used in our experimental design, and then we asked the participants to rate their feelings of regret after the computer presented the obtained and unobtained outcomes. The experimental results revealed that the main effect of stimulation type was significant, which indicated that the influence of the OFC in regret was modulated by tDCS. Furthermore, based on post hoc analyses (Bonferroni), regret was lower in those who received left anodal/right cathodal stimulation than in those who received sham stimulation, which revealed that modulating the activity of OFC reduced the emotional intensity of regret. In addition, an inverted U-shaped curve characterized the mean ratings of regret over time.